Reflections on Using Talanoa Methodology to Engage with Pacific Youth in Aotearoa New Zealand About Their Sexual and Reproductive Health - Cammock, Radilaite; Pousini, Tengihia; Andrews, Malcolm (Taylor & Francis Group, 2025)
Pacific understandings of sexual and reproductive health (SRH) encompass beliefs and practices reflective of Pacific values systems. These are integral to cultural understandings of safety, relationships, and intimacy. Research processes and practices that appropriately address these values and sensitives are scarcely available in the literature, leading to limited use and understanding of culturally appropriate methods and procedures. Pacific methodologies like Talanoa are useful in ensuring that cultural perspectives unique to Pacific youth are addressed and appropriately represented in the research. This paper describes how cultural factors associated with sexual and reproductive health influenced the Talanoa research processes in a study of Pacific youth and SRH education. Key cultural considerations are discussed focussing on the positionality of the researchers, cultural sensitivities and protocols, communication strategies and the role of flexibility in privileging Pacific youth voices.
Keywords: Pacific sexual cultural sensitivities; Pacific youth sexual and reproductive health; sexual and reproductive health education; sexual taboos; Talanoa methods; Pacific sexual cultural sensitivities; Pacific youth sexual and reproductive health; Talanoa methods; sexual and reproductive health education; sexual taboos; 3213 Paediatrics; 32 Biomedical and Clinical Sciences; 42 Health Sciences; Infectious Diseases; Clinical Research; Sexually Transmitted Infections; Prevention; Contraception/Reproduction; Generic health relevance; Reproductive health and childbirth; Adolescent; Female; Humans; Male; Young Adult; Health Knowledge, Attitudes, Practice; New Zealand; Reproductive Health; Sex Education; Sexual Behavior; Sexual Health; Pacific Island People; Humans; Health Knowledge, Attitudes, Practice; Sexual Behavior; Sex Education; Adolescent; New Zealand; Female; Male; Young Adult; Reproductive Health; Sexual Health; Pacific Island People; Adolescent; Female; Humans; Male; Young Adult; Health Knowledge, Attitudes, Practice; New Zealand; Reproductive Health; Sex Education; Sexual Behavior; Sexual Health; Pacific Island People